About my father [videorecording (DVD)] - Earl, Austen; Maniscalco, Sebastian; Maniscalco, Sebastian; De Niro, Robert; Bibb, Leslie; Holm, Anders, 1981-; Rasche, David, 1944-; Dier, Brett, 1990-; Cattrall, Kim (Lionsgate, 2023)
Sebastian is encouraged by his fiancé to bring his Italian hairdresser father Salvo to a weekend get-together to meet her wealthy and eccentric family. As the weekend turns into an outrageous clash of cultures, Sebastian and Salvo discover that the great thing about family is everything about family.